Linking agrarian reform communities to viable supply chains a new perspective in the Department of Agrarian Reform's Development intervention approach - Luz, Gregory Benjamin M.
This paper is a strategy for an organizaional paradigm shift. A shift from the usual practice of production-led delivery of support services to the application of supply chain management concepts. DAR's support service interventions are focused on traditional agricultural commodities and all efforts towards increasing income of farmers are merely efforts to augment subsistence farming. Field implementation of projects for the farmers are highly decentralized and fragmented without a holistic view or a more systemic approach. This paper is a critique on existing approaches to support services by DAR and provides an alternative approach using supply chain management concepts. Recent trends in agricultural marketing shows a promising future for Mindanao Agricultural products specifically on fruits. DAR should be able to perform the role as supply chain manager to effectively link production on the supply side to the market. As a supply chain manager, DAR will be able to make the farmers competitive as part of the supply chain.